Lessons from COVID-19 for behavioural and communication interventions to enhance vaccine uptake - Lewandowsky S; Schmid P; Habersaat K; Nielsen S; Seale H; Betsch C; Böhm R; Geiger M; Craig B; Sunstein C; Sah S; MacDonald N; et al. (United Kingdom, 2025)
The Covid pandemic has yielded new insights into psychological vaccine acceptance factors. This knowledge serves as a basis for behavioral and communication interventions that can increase vaccination readiness for other diseases.